Rising From the Downturn of the Covid-19 Pandemic: Tourism Village Development Strategies through a Community-Based Tourism Approach - Revienda Anita Fitrie; M. Noer Falaq Al Amin; Suci Megawati; Kaheesha Zalfa Rohadatul ‘Aisy (Borong Newinera Publisher, 2023)
Village resilience is one of the concerns in reviving the economy, social, and culture due to the Covid-19 pandemic. Tourism is an aspect that plays an important role in this resilience. The application of development using the concept of a tourist village requires community participation whose development can be done with Community-Based Tourism (CBT). One of the villages that applies the CBT concept is Ketapanrame Village located in Mojokerto Regency, East Java. The researcher used analytical qualitative methods during data collection, capturing the essence of the research objectives through sources. The purpose of this study is to identify the strategies carried out by tourist villages with the application of Community Based Tourism to rise from the downturn of the Covid-19 pandemic in Ketapanrame Village, Mojokerto Regency. The results of this study indicate positive changes in terms of economic, social and cultural aspects of tourism development and innovation carried out by tourism awareness groups.